Implementasi Unclos 1982 Dalam Penyelesaian Sengketa Wilayah Laut Antara Indonesia Dan Tiongkok Di Laut Natuna Utara - Putri, Kesari Pringga Juwita Sedana; Antari, Putu Eva Ditayani; Putra, Komang Satria Wibawa; Sudharma, Kadek Januarsa Adi (Consensus : Jurnal Ilmu Hukum, 2025)
The maritime territorial dispute between Indonesia and China in the North Natuna Sea is a strategic issue in the study of international maritime law. This conflict stems from China's unilateral claim through the nine-dash line concept that overlaps with Indonesia's Exclusive Economic Zone (EEZ). This article is a literature review that aims to analyze the implementation of the 1982 United Nations Convention on the Law of the Sea (UNCLOS) as the international legal basis for resolving the dispute. The study was conducted by examining various previous studies, academic journals, international legal documents, and international court decisions such as the South China Sea Arbitration (Philippines v. China, 2016). The results of the study show that UNCLOS 1982 expressly establishes the sovereign rights of coastal states over natural resources in the EEZ area up to 200 nautical miles as stipulated in Article 57. Meanwhile, China's nine-dash line claim has no internationally recognized legal basis because it contradicts the principle of jus cogens and is not regulated in UNCLOS. Therefore, the implementation of UNCLOS 1982 plays a fundamental role in maintaining legal certainty and upholding Indonesia's maritime sovereignty in the North Natuna Sea. This research is expected to contribute to the development of international legal literature and serve as a reference in formulating maritime dispute resolution policies in the Southeast Asian region.